2021
DOI: 10.3390/ijms222413488
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Changes in Parkinson’s Disease: Lessons from Clinical and Experimental Evidence

Abstract: Dysautonomia is a common non-motor symptom in Parkinson’s disease (PD). Most dysautonomic symptoms appear due to alterations in the peripheral nerves of the autonomic nervous system, including both the sympathetic and parasympathetic nervous systems. The degeneration of sympathetic nerve fibers and neurons leads to cardiovascular dysfunction, which is highly prevalent in PD patients. Cardiac alterations such as orthostatic hypotension, heart rate variability, modifications in cardiogram parameters and barorefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 166 publications
0
19
0
Order By: Relevance
“…The understanding of PD needs to be comprehensive, not just derived from the degeneration of the nigrostriatal system, as the non-motor manifestations are intrinsic to the disease encompassing and encompass several organ systems, with autonomic nervous system dysfunction of particular interest ( Goldstein, 2014 ; Cuenca-Bermejo et al, 2021 ). Cardiovascular changes are a non-motor symptom derived from autonomic dysfunction and commonly seen in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The understanding of PD needs to be comprehensive, not just derived from the degeneration of the nigrostriatal system, as the non-motor manifestations are intrinsic to the disease encompassing and encompass several organ systems, with autonomic nervous system dysfunction of particular interest ( Goldstein, 2014 ; Cuenca-Bermejo et al, 2021 ). Cardiovascular changes are a non-motor symptom derived from autonomic dysfunction and commonly seen in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that about 80%-90% of PD patients will have changes in the autonomic system, and a higher risk of dying due to major cardiac complications than the general population (Palma and Kaufmann, 2018;Scorza et al, 2018;Zhang and Chen, 2020;Gonçalves et al, 2021). Likewise, there is twice the prevalence of heart failure in patients with PD compared to the general population (Cuenca-Bermejo et al, 2021), and these patients are more susceptible to heart failure, coronary artery disease, sudden cardiac death, orthostatic hypotension, hypertension, bradycardia and reduced heart rate variability, pointing to direct changes in the sympathetic and parasympathetic nervous systems (Gonçalves et al, 2020;Finsterer et al, 2018). Therefore, the existence of heart disease needs to be recognized and monitored more intensively in PD, in order to improve the patient's prognosis and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular abnormalities can also appear as a side effect of PD treatment by L-DOPA leading to a decrease in blood pressure aggravating the orthostatic hypotension. This side effect limits the therapeutic use of L-DOPA in geriatric patients with PD and can contribute to the number of hospital admissions ( Cuenca–Bermejo et al, 2021 ). It is estimated that 80% of PD patients have heart rate and blood pressure abnormalities ( Gibbons et al, 2017 ).…”
Section: Cardiovascular and Autonomic Dysfunction And Parkinson’s Dis...mentioning
confidence: 99%
“… 6 Several studies have found autonomic dysfunction to be a valuable predictor of cardiovascular morbidity and mortality in PD patients. 8 , 9 Despite the tremendous clinical and epidemiological relevance of these studies, Sudden Death in PD (SUDPAR), a rare but fatal event, contributes to the increased mortality in PD patients. 2 , 10 …”
mentioning
confidence: 99%